2021
DOI: 10.1159/000518454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polypharmacy on Health-Related Quality of Life in Dialysis Patients

Abstract: <b><i>Introduction:</i></b> Dialysis patients are often prescribed a large number of medications to improve metabolic control and manage coexisting comorbidities. However, some studies suggest that a large number of medications could also detrimentally affect patients’ health-related quality of life (HRQoL). Therefore, this study aims to provide insight in the association between the number of types of medications and HRQoL in dialysis patients. <b><i>Methods:</i></… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The resulting polypharmacy, defined as the use of 5 or more medications ( 10 , 11 ), however, increases the risk of adverse drug–drug or drug–disease interactions and the risk of a “prescription cascade” (ie, the process whereby side effects of drugs are misdiagnosed as symptoms of another medical event and lead to an additional prescription [ 12 ]), which may negatively affect a patient’s HRQOL ( 13 , 14 ). The association between polypharmacy and low HRQOL has been documented for single health conditions such as end-stage kidney disease ( 15 ), arthritis ( 16 ), and cardiometabolic risk factors ( 17 ). However, to date, no study has investigated the impact of polypharmacy on HRQOL in a combined sample of chronic disease patients and patients with multimorbidity by using diverse HRQOL measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting polypharmacy, defined as the use of 5 or more medications ( 10 , 11 ), however, increases the risk of adverse drug–drug or drug–disease interactions and the risk of a “prescription cascade” (ie, the process whereby side effects of drugs are misdiagnosed as symptoms of another medical event and lead to an additional prescription [ 12 ]), which may negatively affect a patient’s HRQOL ( 13 , 14 ). The association between polypharmacy and low HRQOL has been documented for single health conditions such as end-stage kidney disease ( 15 ), arthritis ( 16 ), and cardiometabolic risk factors ( 17 ). However, to date, no study has investigated the impact of polypharmacy on HRQOL in a combined sample of chronic disease patients and patients with multimorbidity by using diverse HRQOL measures.…”
Section: Introductionmentioning
confidence: 99%
“…Because chronically ill patients tend to have a higher risk of multimorbidity, multiple drug use is common (8,9). The resulting polypharmacy, defined as the use of 5 or more medications (10,11), however, increases the risk of adverse drug-drug or drug-disease interactions and the risk of a "prescription cascade" (ie, the process whereby side effects of drugs are misdiagnosed as symptoms of another medical event and lead to an additional prescription [12]), which may negatively affect a patient's HRQOL (13,14). The association between polypharmacy and low HRQOL has been documented for single health conditions such as endstage kidney disease (15), arthritis (16), and cardiometabolic risk factors (17).…”
Section: Introductionmentioning
confidence: 99%
“…They are prescribed on average 9-12 types of medications and have a daily pill burden of 15-19 pills. [1][2][3] A recent study found that a larger number of medications is associated with a lower health-related quality of life (HRQoL) and a higher number of symptoms in dialysis patients. 3 The group of medications contributing most to dialysis patients' pill burden are phosphate binders which comprise 30%-50% of their pill burden.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A recent study found that a larger number of medications is associated with a lower health-related quality of life (HRQoL) and a higher number of symptoms in dialysis patients. 3 The group of medications contributing most to dialysis patients' pill burden are phosphate binders which comprise 30%-50% of their pill burden. 1,2 These drugs are typically prescribed to manage hyperphosphatemia, one of the typical sequelae of chronic kidney disease and an important risk factor for cardiovascular disease and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation